Peningkatan Minat dan Hasil Belajar Siswa Melalui Model PBL kelas VI Fase C di SD Santa Laurensia - Laura Olivia Siregar; Dicky Apriyanto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Action-Based Research aims to enhance the interest and learning outcomes of 6th-grade students at Santa Laurensia Elementary School by implementing the Problem-Based Learning (PBL) model. Low student interest and learning outcomes have been identified as issues in Catholic Religious Studies, necessitating innovative efforts to address them. The research was conducted in two cycles, each involving planning, implementation, observation, and reflection. Data were collected through a learning interest questionnaire, cognitive learning outcome tests (post-tests), and observation sheets related to the ‘Profil Pelajar Pancasila’. The results showed that applying the PBL model significantly increased students' interest in learning, as evidenced by heightened engagement and participation during lessons. Moreover, students' learning outcomes also improved, as demonstrated by comparing post-test scores from cycles I and II. Thus, the PBL model was proven effective in enhancing both the interest and learning outcomes of 6th-grade students in Phase C at Santa Laurensia Elementary School.